APLIKASI ONLINE PEMILIHAN LAPTOP DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) (Information Technology and Telematics, 2014)
Abstract--Laptop is a portable computer device that has the exact same functionality with Desktop Computers / PC Desktop. Specificity of the laptop has a design that is relatively small when compared with the Desktop Computer. The development of technology, the laptop developed by each brand with a variety of features. Design changes experienced rapid growth, both in terms of design, speed of the laptop, as well as additional features are incomplete at this time, laptops are also sold at relatively low prices and can customize the user budget. It can be used as an alternative to having an electronic device users laptop with a relatively affordable price. One of the methods that assist consumers in choosing a laptop is Analytic Hierarchy Process (AHP). AHP method is used for calculating weights based on predetermined criteria. The objective is to create a software web-based applications that can provide convenience to all the people who want to buy a laptop by using several criteria, so that a decision can be taken to establish the best laptop with criteria determined by the method (Analytical Hierarchy Process) AHP . Keyword-- laptop, AHP, developer, web.